Antioxidant Baccharis trimera Leaf Extract Suppresses Lipid Accumulation in C. elegans Dependent on Transcription Factor NHR-49 - Flávia Roberta Monteiro Souza; Giovanna Melo Martins Silva; Cesar Orlando Muñoz Cadavid; Lucas dos Santos Lisboa; Maylla Maria Correia Leite Silva; Weslley Souza Paiva; Marcelo José Pena Ferreira; Riva de Paula Oliveira; Hugo Alexandre Oliveira Rocha (MDPI AG, 2022)
Obesity is a global public health problem that is associated with oxidative stress. One of the strategies for the treatment of obesity is the use of drugs; however, these are expensive and have numerous side effects. Therefore, the search for new alternatives is necessary. Baccharis trimera is used in Brazilian folk medicine for the treatment of obesity. Here, B. trimera leaf extract (BT) showed antioxidant activity in seven in vitro tests, and it was not toxic to 3T3 murine fibroblasts or Caenorhabditis elegans. Furthermore, BT reduces the intracellular amount of reactive oxygen species and increases C. elegans survival. Moreover, these effects were not dependent on transcription factors. The inhibition of fat accumulation by BT in the C. elegans model was also investigated. BT reduced lipid accumulation in animals fed diets without or with high amount of glucose. Furthermore, it was observed using RNA interference (iRNA) that BT depends on the transcription factor NHR-49 to exert its effect. Phytochemical analysis of BT revealed rutin, hyperoside, and 5-caffeoylquinic acid as the main BT components. Thus, these data demonstrate that BT has antioxidant and anti-obesity effects. However, further studies should be conducted to understand the mechanisms involved in its action.